Better Safe Than Sorry : How Consumers Navigate Exposure to Everyday Toxics - MacKendrick, Norah (Book collections on Project MUSE., 2018)
"How toxic are the products we consume on a daily basis? Whether it's triclosan in toothpaste, formaldehyde in baby shampoo, endocrine disruptors in water bottles, or pesticides on strawberries, consumers are increasingly concerned about the chemicals in their food and personal care products. This book chronicles how ordinary people try to avoid exposure to toxics in grocery store aisles using the practice of 'precautionary consumption.' Through an innovative analysis of environmental regulation, the advocacy work of environmental health groups, the expansion of the health-food chain Whole Foods Market, and interviews with consumers, Norah MacKendrick ponders why the problem of toxics in the U.S. retail landscape has been left to individual shoppers--and to mothers in particular. She reveals how precautionary consumption, or 'green shopping, ' is a costly and time-intensive practice, one that is connected to cultural ideas of femininity and good motherhood but is also most available to upper- and middle-class households. Better Safe Than Sorry powerfully argues that precautionary consumption places a heavy and unfair burden of labor on women and does little to advance environmental justice or mitigate risk."--Provided by publisher.